Physicochemical Study of 'Dolomitic' Sorbents Prepared under Different Thermal Conditions. Part II. Sintering as a Result of Long-term Heating - Elzbieta Stefaniak; Bogdan Biliński; Piotr Staszczuk; Jan Wójcik (Adsorption Science & Technology)
The influence of prolonged heating (12,24 and 46 h) on the porous structure and surface properties of 'dolomitic' sorbents was investigated. No important changes in the specific surface areas were found. However, increasing the heating time resulted in a decrease in the total pore volume and the average pore radius as well as considerable differences in the pore size distributions. These changes may be explained by the effect of sintering which accompanies many gas-solid reactions. The adsorption properties of the sorbents towards hydrocarbons were also investigated and the adsorption energy distribution functions calculated. The investigated surfaces appeared to be strongly heterogeneous.